Burden of Blood Pressure–Related Alleles Is Associated With Larger Hematoma Volume and Worse Outcome in Intracerebral Hemorrhage - Falcone, Guido J.; Biffi, Alessandro; Devan, William J.; Brouwers, H. Bart; Anderson, Christopher D.; Valant, Valerie; Ayres, Alison M.; Schwab, Kristin; Rost, Natalia S.; Goldstein, Joshua N.; Viswanathan, Anand; Greenberg, Steven M.; et al. (Stroke (1970), 2013)
Intracerebral hemorrhage (ICH) is the acute manifestation of a progressive disease of the cerebral small vessels. The severity of this disease seems to influence not only risk of ICH but also the size of the hematoma. As the burden of high blood pressure-related alleles is associated with both hypertension-related end-organ damage and risk of ICH, we sought to determine whether this burden influences ICH baseline hematoma volume. Prospective study in subjects of European descent with supratentorial ICH who underwent genome-wide genotyping. Forty-two single nucleotide polymorphisms associated with high blood pressure were identified from a publicly available database. A genetic risk score was constructed based on these single nucleotide polymorphisms. The score was used as the independent variable in univariate and multivariate regression models for admission ICH volume and poor clinical outcome (modified Rankin Scale, 3-6). A total of 323 ICH cases were enrolled in the study (135 deep and 188 lobar intracranial hematomas). The blood pressure-based genetic risk score was associated with both baseline hematoma volume and poor clinical outcome specifically in deep ICH. In multivariate regression analyses, each additional SD of the score increased mean deep ICH volume by 28% (or 2.7 mL increase; β=0.28; SE=0.11; P=0.009) and risk of poor clinical outcome by 71% (odds ratio, 1.71; 95% confidence interval, 1.05-2.80; P=0.03). Increasing numbers of high blood pressure-related alleles are associated with mean baseline hematoma volume and poor clinical outcome in ICH. These findings suggest that the small vessel vasculopathy responsible for the occurrence of the hemorrhage also influences its volume.